A Qualitative Study of Leader Transition and Polarities. (August 2016) - Manderscheid, Steven; Harrower, Nancy L.
The Problem: Leaders frequently transition from one organization into another. Leader transitions can be fraught with challenges as new leaders try to adapt to a new culture, team, and work processes. At no time during their career are leaders more vulnerable to failure as when they are in transition. The Solution: The purpose of this qualitative study was to explore leader transition and polarity. The researchers identified whether polarities existed during a leader's transition from one leadership role into another and identified strategies leaders use to manage such polarities. Five polarities were identified: (a) Drive Change/Maintain Status Quo, (b) Work/Family, (c) Tradition/Innovation, (d) Action/Reflection, and (e) Task/Relationships. Furthermore, five strategies were used to manage polarities: (a) Collaborating, (b) Learning, (c) Developing Talent, (d) Reflecting (on Self), and (e) Decision-Making. By understanding the concepts and ramifications of polarities, it is hoped that newly transitioning leaders will be able to recognize and adjust to situations in which polarities may arise. Stakeholders: The stakeholders include leaders in transition, leadership development professionals, executive coaches, and human resource management. These professionals should consider this research when they work to develop the capacity of their leadership talent.